DETERMINATION OF CAREER DEVELOPMENT AND PERFORMANCE: ANALYSIS OF JOB PROMOTION AND EMPLOYEE TRANSFER (HUMAN RESOURCE MANAGEMENT LITERATURE REVIEW) - Achyar Mubarok, Aulia (Dinasti Publisher, 2022)
Previous research is a very important thing in the preparation of a scientific article. The purpose of previous research or relevant research is to strengthen the theory and phenomena of the relationship or influence among variables. This article reviews the Determination of Career Development and Performance: Analysis of Job Promotions and Employe Transfer, a Human Resource Management Literature Review. Writing this article aims to build a hypothesis of the influence between variables to be used in further research. The results of this library research are: 1) Job Promotion has an effect on Career Development; 2) Employee Transfers have an effect o Career Development; 3) Job Promotion has an effect on Performance; 4) Employee Transfer has an effect on Performance; and 5) Career Development has an effect on Performance.